Implementation of PjBL using unila’s moodle v-class and its interaction of students’ intrinsic factors - Dina Maulina; Nadya Meriza; Median Agus Priadi; Ismu Sukamto (Biosfer: Jurnal Pendidikan Biologi, 2022)
The Main Performance Indicators (IKU) of Higher Education, it has been a mandate the implementation of learning that aims to build and create collaborative and participatory classes. The purpose of this study was aims to analysis the linearity between the implementation of PjBL-based learning using Unila’s Moodle v-class with students' intrinsic factors in learning Animal Structure during online learning in realizing collaborative and participatory classes. This research is an experimental-research with posttest-only control design with the population in this study are students of biology education at the University of Lampung, amounting to 371 people. The sample was obtained using purposive sampling technique, as much as 124 students who had taken the Animal Structure course. The results showed that there was a significant difference (p<0.05) in student learning outcomes in the control and experimental classes. Nevertheless, there was no influence of intrinsic factors on PjBL results in both classes (p<0.05), all students had high intrinsic factors to take part in online learning is high, however the optimizing learning outcomes is not linear.